Integrating Marine Tourism into the Blue Economy Framework - REDDY, Kiran; SAILESH, Bhaskar (Journal of Environmental Management and Tourism, 2024)
Marine tourism is an integral part of the blue economy, contributing significantly to economic development and environmental sustainability. This paper explores the various dimensions of marine tourism within the blue economy framework, emphasizing its economic, social, and environmental impacts. The conceptual framework defines marine tourism activities and highlights their importance. Current trends and practices in marine tourism are analyzed, along with their economic implications and the resulting environmental and social impacts. The paper also delves into governance models, focusing on public-private partnerships and the role of non-governmental organizations (NGOs) in promoting sustainable tourism practices. National and regional policies are examined through case studies and comparative analysis. The economic integration of marine tourism with other blue economy sectors, such as fisheries and coastal infrastructure, is discussed, highlighting the revenue generation and economic diversification benefits. The findings underscore the need for effective governance, stakeholder engagement, and adaptive management to achieve sustainable marine tourism development.